Synthesis, characterization, biocidal and virucidal properties of metal oxide nanoparticles - Haggstrom, Johanna A. (Kansas State University, 2009)
Non-polar halogens (Cl2, Br2 and I2) and polar interhalogen molecules (ICl, IBr and ICl3) have been adsorbed on the surface of several high surface area materials, including three different nanosized metal oxides (NanoActive® (NA) Al2O3 Plus, NA-TiO2 and NA-CeO2). The prepared halogen and interhalogen adducts have been characterized in detail by thermogravimetric analysis (TGA), UV-Vis, Raman and X-ray photoelectron spectroscopies (XPS) and the results are discussed herein. The different metal oxides lead to varying strength of adsorption of the halogen/interhalogen in the prepared adducts and adsorption is stronger in the nanosized metal oxides as compared to their macrocrystalline available counterparts. Nanosized metal oxide halogen adducts possess high surface reactivities due to their unique surface morphologies. These adducts have been used as reactive materials against vegetative cells, such as Escherichia coli and Bacillus megaterium, as well as spores, including Bacillus subtilis and Bacillus anthracis (Δ Sterne strain). High biocidal activities against both Gram-positive and Gram-negative bacteria, as well as spores have been obtained. Bactericidal test procedures include a water suspension method and a dry membrane method and the results illustrate that good results are obtained using both procedures. Transmission electron micrographs have been used to illustrate the treated and untreated cells and spores, giving insight into the mechanism. It is proposed that the abrasive character of the particles, along with the oxidative power of the halogens/interhalogens as well as the electrostatic attraction between some of the metal oxides and the biological material are main reasons for the high biocidal activities. Three different bacteriophages (MS2, φX174 and PRD1) have also been studied and initial results indicate that there is big potential for the use of metal oxide halogen and interhalogen adducts for the destruction of viruses. Other potential uses for them also include halogenating agents in organic and inorganic synthesis as well as a safe way to store intact halogens.
Keywords: Metal oxides; Halogens; Biocidal; Virucidal; Nanoparticles; Chemistry, Inorganic (0488)